A life course perspective on the travel of Australian millennials. (October 2017) - Delbosc, Alexa; Nakanishi, Hitomi
Abstract: Recent research suggests that the millennial generation may be inclined to more sustainable travel habits than previous generations, reflected in lower rates of driver licensing in many countries and greater use of sustainable modes in others. However, it is still unknown whether millennials will continue to use sustainable transport modes as they age, or whether their travel patterns will revert to the car dependence displayed by previous generations. This research addresses this overlooked area in the travel behaviour research through an in-depth, qualitative prospective exploration of the interactions between life course and mobility of millennials in three Australian cities (Sydney, Melbourne and Canberra). Drawing from life-course transition research, fifty-five in-depth interviews found that Australian millennial life courses could be categorised into three typologies: (a) traditional, (b) delayed-traditional and (c) non-traditional/uncertain. In addition, millennial mobility was categorised into four typologies: (a) choice multi-modals, (b) captive multi-modals, (c) choice drivers and (d) captive drivers. Many millennials preferred living in inner urban areas, were multi-modal and somewhat 'mode-agnostic, ' open to using whatever travel mode best suited their needs; very few showed a strong preference for cars. However, the research does suggest that as millennials approach adult milestones such as having children, the difficulty in finding suitable housing near transit may push some of them into neighbourhoods where sustainable transport is no longer a practical option. Policy interventions that support a sustainable lifestyle are suggested and research directions are discussed.